(untitled) (Acta Entomologica Serbica, 2019)
Laboratory tests were conducted to evaluate the efficacy of three diatomaceous earth (DE) formulations; Celite 209, DiaFil 610 and SilicoSec in three wheat varieties, Atilla-Gan-Atilla, Cetia and Seri M82, against Rhyzopertha dominica (F.). The DE formulations were applied at four dose rates; 250, 500, 750 and 1000 mg/kg. Bioassays were carried out at 26-34°C and at 32-45 % relative humidity (RH). Efficacy was evaluated by recording adult mortality after 7 and 14 days, and progeny production at 56 and 112 days after treatment (DAT). Adult mortality levels significantly differed among varieties, exposure periods, DE formulations and their dose rates, ranging from 27.7 to 100 %. With all DE formulations and wheat varieties, complete adult mortality was achieved at 1000 mg/kg and 14 days of exposure. SilicoSec was more effective, proving higher mortality within shorter exposure period than other formulations. Progeny production was signiﬁcantly higher in untreated Cetia than in the two other varieties and always greater in untreated than treated grains. Complete progeny suppression was recorded at ≥750 mg/kg. Generally, the performance of all DE formulations was greater in Atilla-Gan-Atilla and Seri M82 compared to Cetia.